Nemzetközi összehasonlító szociológiai vizsgálat a nemzeti identitásról (Szociológiai Szemle, 2024)
In the framework of the International Social Science Project a cross-national survey was carried out in 1996 on representative samples of 23 countries of the world. The  participating coutries represent East European, West European countries as well  the US, Australia, New Zealand, Japan and Philippines. Multivariate analyses of  the data showed that the present-day empirical patterns of national identification do  not correspond with historical types of national formation. In order to reveal  specific effects of class, age, and gender on national identification further analyses  are needed.